Integrasi Dakwah dan Pendidikan pada Gerakan Wahdah Islamiyah: Perspektif Dakwah Islam Kontemporer: Integrating Da‘wah and Education in the Wahdah Islamiyah Movement: A Contemporary Islamic Perspective - Iskandar; Samsuddin; Abdul Jabar Idharudin; Agusman (AL-QIBLAH: Jurnal Studi Islam dan Bahasa Arab, 2026)
This article examines the integration of da‘wah and education in the Wahdah Islamiyah Movement from the perspective of contemporary Islamic da‘wah, positioning da‘wah as an educational and social transformation process. The study aims to analyze the forms, mechanisms, and implications of integrating da‘wah and education in shaping Muslim character and strengthening socio-religious engagement. This research employs a qualitative approach using a case study method, with data collected through in-depth interviews, participant observation, and document analysis of educational systems, da‘wah programs, and cadre development practices within Wahdah Islamiyah. The findings reveal that Wahdah Islamiyah implements a systematic, structured, and sustainable integration of da‘wah and education based on Ahl al-Sunnah wa al-Jama‘ah theology, tiered tarbiyah models, comprehensive da‘i cadre formation, the use of digital da‘wah media, and da‘wah bil-hal through educational and social empowerment programs. The da‘i cadre system serves as the central nexus between da‘wah and education, functioning not merely to produce preachers but also educators and agents of social change characterized by the 5M values (Mu’min, Muslih, Mujahid, Muta‘awin, and Mutqin). This study contributes to contemporary Islamic da‘wah scholarship by offering an integrative da‘wah-educational model that is adaptive, participatory, and contextually responsive to modern societal challenges.